Speech therapy procedures in high-risk newborns - doi:10.5020/18061230.2010.p175 - Júlia Valéria Lima Pinheiro; Nirley Moreira de Oliveira; Hipólito Virgílio Magalhães Júnior (Universidade de Fortaleza, 2012)
Methods: A documental research based on registration records, comprised by a total of 34 newborns that required early stimulation by the speech therapy service in a neonatal ICU of a hospital with tertiary level of care. The study was held in the period between August, 2005 and January, 2006. From the sample, 14 children were female (41.2%) and 20 were male (58.8%). The age of the newborns ranged from 3 to 57 life days. The studied variables included: risk conditions of the newborn, clinical assessment procedures, the intervention performed and the results obtained regarding weight. Results: The risk condition of preterm newborn (PTNB) associated with respiratory distress syndrome (RDS) was present in 25 (73.5%) children. The initial weight of 15 (44.11%) children ranged from 1170 to 1742 grams. The most widely discussed speech therapy procedures were the assessment of oral functions with identification of changes in sucking and swallowing in 25 (73.5%) newborns and intervention by means of non-nutritive sucking in 18 (53%) children. At the end of speech therapy, 19 (55.9%) children weighed between 1742 to 2314 grams. Conclusions: The benefits of speech therapy performance were related to the identification of high-risk children who required intervention in oral functions and organization of the baby for feeding. It is assumed that the introduction of oral administration as quickly and safely as possible favored the improvement of the nutritional status of children and their clinical evolution.